2019
DOI: 10.1186/s12885-019-6097-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized-controlled, single-blind trial to improve quality of life with stereotactic body radiotherapy for patients with painful bone metastases (ROBOMET)

Abstract: Background Bone metastases represent an important source of morbidity in cancer patients, mostly due to severe pain. Radiotherapy is an established symptomatic treatment for painful bone metastases, however, when conventional techniques are used, the effectiveness is moderate. Stereotactic body radiotherapy (SBRT), delivering very high doses in a limited number of fractions in a highly conformal manner, could potentially be more effective and less toxic. Methods This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…32 Results of more ongoing RCTs are needed to determine the role of SBRT in the palliative treatment of bone metastases. 26,33,34 We showed that the duration of the response and the percentages of ongoing pain responses did not differ, despite the higher complete response rates at certain follow-up time points in the SBRT group. In addition, patients showed fluctuating pain responses during follow-up.…”
Section: [46%]mentioning
confidence: 75%
“…32 Results of more ongoing RCTs are needed to determine the role of SBRT in the palliative treatment of bone metastases. 26,33,34 We showed that the duration of the response and the percentages of ongoing pain responses did not differ, despite the higher complete response rates at certain follow-up time points in the SBRT group. In addition, patients showed fluctuating pain responses during follow-up.…”
Section: [46%]mentioning
confidence: 75%
“…Indeed, several studies have been published comparing the effectiveness between SBRT and conventional RT [32][33][34][35][36][37]. Indeed, there are potential disadvantages of SBRT, including possible increased pain flare or a higher incidence of radiation-induced fractures [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have been published comparing the effectiveness between SBRT and conventional RT [ 32 37 ]. Indeed, there are potential disadvantages of SBRT, including possible increased pain flare or a higher incidence of radiation-induced fractures [ 38 ]. However, if a dose-escalated approach within the context SBRT could improve the pain response to radiotherapy and reduce acute toxicity, this would have a significant impact on the QoL for a large number of patients with advanced metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, our center is evaluating SABR in the setting of antalgic treatment for bone metastases. 21 In that trial, patients are simulated and treated in 1 day, suggesting that it is feasible to give these high-precision treatments to all patients.…”
Section: Discussionmentioning
confidence: 99%